مخالفات الرازي لأبي مسلم الأصفهاني في تفسيره الكبير– الجزء الأول من سورة البقرة نموذجاً - عرض ودراسة نقدية - El- Kubesi, A. A. K.; Mustafa Shehade, M. M. S. (Universiti Sains Islam Malaysia, 2024)
This research is aimed at exploring interpretation differences in Surah al-Baqarah between Abu Muslim al-Asfahani (d. 322AH/933CE) and Fakhr al-Din al-Razi’s (d. 606/1210) al-Tafsir al-Kabir. Through critical study to uncover the character of these differences, comparing their interpretations with other exegetes as well as correlating their thought with the Quranic exegesis and its sciences, this study demonstrates that a possible tarjih (choosing between existing opinions) can be inferred on this matter. This approach facilitates to address the character of these differences at establishing their arguments that were supported with valid evidences. Hence, the study employs inductive analytical evidence-based approach that traces the controversial issues between Abu Muslim al-Asfahani and al-Razi in the first juz’ (part) of Surat al-Baqarah until verse 115 in al-Tafsir al-Kabir. To summarize the article, al-Razi's opposition to the opinions of Abu Muslim essentially followed the principles of Quranic exegesis and its sciences in addition to the advocacy of majority of Muslim scholars.